Adventures with Waffles : Vaffelhjarte Series #1 - Parr, Maria, 1981-; Forrester, Kate, (Illustrator); Puzey, Guy (Somerville, Massachusetts : Candlewick Press, 2015)
Young Trille struggles with the fear that nothing will ever be right again when his best friend moves and his waffle-making Auntie Granny passes away.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Secrets -- Fiction; Friendship -- Fiction; Secrecy -- Fiction